Literature Review : Pengaruh Faktor Sosial Ekonomi Terhadap Tindakan Kejahatan Pencurian Sebagai Mata Pencaharian - Nurfath, Al Fachri; Manik, Samantha Petricia; Prameswari, Audria Sharon; Maulitya, Tannya Athalla; Supriyadi, Tugimin (Media Hukum Indonesia (MHI), 2024)
The phenomenon of economic inequality is a problem that deserves attention, because it can become a social problem. One of the social problems caused by economic inequality is crime. Crime itself is often defined as a behavior that violates the law so that a person can be entangled with the law. Poverty has a major influence on the encouragement of criminal behavior both in the long and short term. This research uses the Literature Review study method by collecting, evaluating, and synthesizing all papers relevant to a particular research topic. The purpose of the literature review is to present a comprehensive understanding of the existing literature and identify knowledge gaps that justify further research. the data source used in this research is secondary data. Based on the results of a review of 5 journals that have been conducted, many factors can influence the occurrence of crime, but generally socio-economic factors are a big reason that causes a person to decide to commit the crime of theft. Socioeconomic factors themselves are caused by a person's inability to fulfill their daily needs, as a result of their employment status and social status.